Investigation Into Impact of Cost Reduction Techniques as Measure of Increasing Survival: case of SNV Netherlands Development Organisation - Musabaike, Chido (2017)
The research sought to investigate the impact of cost reduction techniques as a measure of increasing the chances of survival: A case of SNV Netherlands development organisation. The funding for SNV from the Dutch government was reduced due to the general cuts in the Dutch government. Therefore, this bought the need for the organisation to reduce costs in order to survive in the short run. Literature was reviewed being guided by the objectives. Other authors reviews on cost reduction techniques that are currently implemented by SNV were assessed. The researcher used combined mixed approach which include qualitative and quantitative research methods. Cost reduction techniques increase the chances of survival in the long run.